Шляхи вдосконалення системи судоустрою України в умовах викликів сьогодення - Бабкова, Т. В.; Babkova, T. V.; Тесленко, І. О.; Teslenko, I. O. (Актуальні проблеми правознавства. - 2023. - Вип. 4 (36). - С. 45-50, 2023)
Досліджено шляхи оптимальної структури утворення ланок спеціалізованих судів у системі судоустрою, зокрема розглянуто вказану проблему на прикладі такої вертикалі спеціалізованих судів, як господарські, здійснено аналіз суперечностей, прогалин та неузгодженості законодавства, з метою оптимізації витрат на утримання судів у складних умовах військового стану для бюджету України, забезпечення ефективності та пропорційності навантаження під час їхньої діяльності.

The article is devoted to the problem of improving the structure of courts with a view to protecting the rights of all members of society, ensuring a real opportunity for access to justice, optimizing the costs of maintaining courts, and making their activities more efficient. Based on the analysis of the current legislation, the authors of the article analyze and characterize the fundamental principles of the court system, namely, territoriality, specialization and instance, as well as the components of the vertical of the judicial system, with a view to creating and operating an optimal system of higher specialized courts for resolving certain categories of cases. To this end, the author examines the issues of optimization of the structure of the judicial system of Ukraine in terms of expediency, proportional distribution of the workload and reduction of budgetary expenditures. The authors of the article analyze the possibility of using the existing resources of local general courts, together with the use of the existing human resources of the judicial system and the widespread introduction of new technical capabilities, ensuring citizens’ access to the available electronic services, and moving away from the expediency of hearing cases in a particular city (a particular court building). In particular, the author analyzes and weighs the feasibility of maintaining them as courts of a separate specialization in the context of further judicial reform using the example of the economic courts vertical.

Исследованы пути оптимальной структуры образования звеньев специализированных судов в системе судоустройства, в частности рассмотрена указанная проблема на примере такой вертикали специализированных судов, как хозяйственные, осуществлен анализ противоречий, пробелов и несогласованности законодательства с целью оптимизации расходов на содержание судов в сложных условиях военного положения для бюджета Украины, обеспечения эффективности и пропорциональности нагрузки во время их деятельности.
Ways to Improve the Judicial System of Ukraine in the Context of Current Challenges
Keywords: структура судів; доступ до правосуддя; спеціалізовані суди; система судоустрою; господарські суди; реформування; військовий стан; structure of courts, access to justice, specialized courts, judicial system; access to justice; specialized courts; judicial system; commercial courts; reformation; martial law; структура судов; доступ к правосудию; специализированные суды; система судоустройства; хозяйственные суды; реформирование; военное положение